Mapping the Landscape: Malaysian Muslim Women's Insights on Human Milk Banking Through the Islamic Lens - Win, Nilar; Ismail, Hamizah; Mohammad Aidid , Edre; Hashi , Abdurezek Abdulahi (IIUM Medical Journal Malaysia, 2025)
INTRODUCTION: Donated human milk in human milk bank (HMB) is healthier for preterm babies compared to formula milk. In 2022, Halimatussaadiah milk bank was established in Pahang, Malaysia. The objective of this study was to determine the knowledge, attitudes, and behaviours of Malaysian Muslim mothers towards HMB and its Islamic perspectives. MATERIALS AND METHODS: From July 2021 to January 2023, a Pahang state multicentred cross-sectional study was carried out at Sultan Ahmad Shah Medical Centre, Hospital Tengku Ampuan Afzan, and Hospital Sultan Haji Ahmad Shah. 793 Muslim Malaysian women who had delivered and breastfed at least one child before, completed validated self-administered Google Form questionnaires, encompassing knowledge, attitude, and behaviour towards HMB. RESULTS: The participants, averaging 32.67 years old, were mostly well-educated with an average of 2 children and a monthly household income of approximately MYR 4,500.00. 62.3% recognized HMB as a crucial element for the wellbeing of premature infants. Strong support for Shariah-compliant HMB was evident, with 64.3% advocating for donor-recipient identity disclosure. 34.9% were open to their babies receiving milk from multiple donors, although opinions were divided on accepting milk from non-Muslim women in life-threatening situations, and their willingness to donate breastmilk, both to known and unknown babies. Out of 793 women, only 1.3% had donated their breast milk to HMB. Yet, 45.6% were willing to volunteer and give their milk to a Shariah compliant HMB. CONCLUSION: Generally, Malaysian Muslim women in Pahang showed a strong acceptance to the establishment of HMB provided that religious concerns were appropriately addressed.